A semantic similarity calculation model for event ontology mapping. (2018) - Wang, Xu; Liu, Wei; Tan, Yue
Ontology mapping is quite a useful solution for matching semantics between ontologies or schemas that were designed independently of each other. The traditional ontology is mainly to describe concepts and hierarchy relations between concepts, which easily cause 'tennis problem' and impact the accuracy of concept mapping, especially while integrating data in event-centred domains. In this paper, we give the definition of event ontology mapping, and then propose a semantic similarity calculation model for event ontology mapping, which enable the mapping between event-based information with more abundant semantics, and especially enable the semantic mapping between event elements in different event classes. Experiments show that the proposed model can effectively identify the semantic relations of event classes in two event ontologies.